2012
DOI: 10.1038/bmt.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Viral loads and antiviral resistance of herpesviruses and oral ulcerations in hematopoietic stem cell transplant recipients

Abstract: Ulcerative oral mucositis and infection are frequent complications in hematopoietic stem cell transplant (HSCT) recipients. The aim of this study was to investigate the relationship between oral ulcerations and HSV-1, EBV and CMV excretion and the presence of aciclovir-resistant HSV-1 strains in HSCT recipients. This prospective observational study included 49 adult patients who underwent allogeneic HSCT. In total, 26 patients received myeloablative and 23 received non-myeloablative conditioning. Ulcerations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
2
31
0
11
Order By: Relevance
“…When assessing clinical significance of the post-transplant viremia, we revealed a clear dependence between HSV viremia and oral mucositis grade, in accordance with results reported by van der Beek et al 1 Indeed, we have found a significant increase in oral ulceration rates among HSV-positive vs HSV-free cases (100% vs 75%, respectively; Po0.02).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…When assessing clinical significance of the post-transplant viremia, we revealed a clear dependence between HSV viremia and oral mucositis grade, in accordance with results reported by van der Beek et al 1 Indeed, we have found a significant increase in oral ulceration rates among HSV-positive vs HSV-free cases (100% vs 75%, respectively; Po0.02).…”
supporting
confidence: 80%
“…We have read with great interest an article by van der Beek et al 1 published in Bone Marrow Transplantation. The authors reported that HSV-1 shedding in oral fluid after hematopoietic SCT (HSCT) is a significant predictor for oral mucosal ulcerations in adult patients, thus being a promising marker of the epithelial lesion.…”
mentioning
confidence: 91%
“…There was statistically significant difference compared to all other excreted viruses ( p  < 0.001). Ambinder et al and Van der Beek et al stated that 25%–98% of the saliva samples of immunosuppressed patients were positive for EBV as a result of chemotherapy [14,39]. According to the authors, all cancer patients presented some degree of immunosuppression, which may explain the higher rates of EBV excretion.…”
Section: Discussionmentioning
confidence: 99%
“…The association between viral infections and oral complications from RT are poorly reported in the literature, and the existing results are contradictory. Some authors suggest that RT may cause a transient state of immunosuppression, thus contributing to reactivation of herpesviruses [14]. Until this moment, there have been few studies in the literature relating oral shedding of human herpesviruses to xerostomia in patients undergoing RT associated with chemotherapy [1517].…”
Section: Introductionmentioning
confidence: 99%
“…The carriers of of HSV-1 were found in 80% of patients before HSCT. Researchers state that the persistence of HSV-1 infection in spite of the treatment with acyclovir, affected approximately 18% of patients, and probably was the result of a mutation located in a TK gene (thymidine kinase) [7,8].…”
Section: Discussionmentioning
confidence: 99%